Haiti : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper focuses on Haiti near and medium-term challenges and policy priorities and was prepared before coronavirus disease 2019 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. The outbreak has greatly amplified uncertainty and downside risks around the outlook. The IMF staff is closely monitoring the situation and will continue to work on assessing its impact and the related policy response in Haiti and globally. Income inequality can hamper economic growth and development. Currently, the financial needs of the rural poor are sustained by microfinance institutions, financial cooperatives, humanitarian programs, and remittance providers. Greater financial inclusion could also be reached via solutions outside of traditional banking practices, including through fintech initiatives. In addition to being a moral imperative, addressing gender inequality is necessary for generating broad-based and inclusive growth. Formal employment opportunities for women need to be expanded. A good start would be to implement the 30 percent quota reserved for women in public-sector appointments, which was introduced in 2012 but never enforced.